Perception of School Committee Members (SCMs) on Factors Contributing to Overweight and Obesity Among High School Students in Kiribati: A Qualitative Study - Tanebu J. Tong; Masoud Mohammadnezhad; Nasser Salem Alqahtani; Mosese Salusalu (Frontiers Media S.A., 2022)
BackgroundSchools are vital settings for overweight and obesity prevention among children and adolescents. School Committee Members (SCMs) are crucial assets to engaging students with overweight and obesity prevention programs. This study aimed to determine factors contributing to overweight and obesity among high school students in Kiribati through the perception of SCMs.MethodsThis prospective qualitative study was conducted in four randomly selected senior high schools in South Tarawa, Kiribati, from August to November 2020. With a purposive selection of 20 SCMs employed at the four high schools, both male and female participants consented to participate in the study. A semi-structured open-ended questionnaire was used for data collection using focus group discussions (FGDs). Data were transcribed and analyzed using the thematic analysis method.ResultsTwenty participants were involved in FGDs with equal number of SCMs (n = 5) who attended FGDs for each school and 45% of them were female participants. Six themes were identified, namely, knowledge, behaviors, perceived status toward overweight and obesity, perceived action benefits, perceived barriers to practices, and proposed strategies to overweight and obesity prevention. These themes reveal that SCMs have a broad understanding and skill set for overweight and obesity causes and effects. However, the aptitude alone is not enough to prevent the occurrence, and thus, proposed feasible plans were voiced for responsible stakeholders to include in policy developments for overweight and obesity prevention.ConclusionThis study recognized that the knowledge-behavior gap is the main reason behind the failure in preventative strategic approaches among adolescents. As role models to students, SCMs and their schools should team up in implementing the public health policies and building mutual awareness and understanding with students and other specialist stakeholders for a more momentous and viable impact.